2014
DOI: 10.1038/srep04281
|View full text |Cite
|
Sign up to set email alerts
|

Light induced conch-shaped relief in an azo-polymer film

Abstract: We have discovered that a novel chiral structured surface relief (termed 'conch'-shaped surface relief) with a height of over 1 mm can be formed in an azo-polymer film merely by employing circularly polarized optical vortex irradiation with a total angular momentum of j 5 62. The temporal evolution of the conch-shaped surface relief in the azo-polymer film was also observed. The results provide physical insight into how the angular momentum of light is transferred to a material through mass transport by cis-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(47 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…More importantly, vortex laser pulses, carrying simultaneously orbital (OAM) and spin (SAM) angular momenta, were demonstrated to twist transiently molten metal producing chiral-shaped micron-size needles [10,11]. Later, similar effects were used to produce chiral structures on the surface polymers [12][13][14] and semiconductors [15,16]. Based on their experiments with ablation of bulk tantalum targets [17], the authors revealed that mass transfer and handedness of the produced surface structures are associated with corresponding phase helicity (or OAM), while the polarization helicity (or SAM) accelerates/decelerates the movement of the molten material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, vortex laser pulses, carrying simultaneously orbital (OAM) and spin (SAM) angular momenta, were demonstrated to twist transiently molten metal producing chiral-shaped micron-size needles [10,11]. Later, similar effects were used to produce chiral structures on the surface polymers [12][13][14] and semiconductors [15,16]. Based on their experiments with ablation of bulk tantalum targets [17], the authors revealed that mass transfer and handedness of the produced surface structures are associated with corresponding phase helicity (or OAM), while the polarization helicity (or SAM) accelerates/decelerates the movement of the molten material.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a number of papers an alternative pioneering approach, employing optical radiation with specially designed intensity-, polarization-or phase states, was proposed for fabrication of chiral structures [9][10][11][12][13][14][15][16][17][18][19]. In particular, using inherent chirality of nanoparticles, synthesis of twisted nanoribbons through self-assembly in water solution under irradiation with continuous-wave circularly polarized laser radiation was demonstrated * alex.iacp.dvo@mail.ru [9].…”
Section: Introductionmentioning
confidence: 99%
“…They have potential applications in a variety of research areas, such as optical trapping and manipulation1314, terabit high-speed optical communications1516, and chiral or achiral nanostructure fabrication1718192021. Laguerre-Gaussian (LG) modes, which are eigen modes of the para-axial electromagnetic equation in cylindrical coordinates, are well known as conventional optical vortices.…”
mentioning
confidence: 99%
“…Since Allen et al [1] demonstrated that a Laguerre-Gaussian (LG) beam with the azimuthal phase structure exp (i φ) carries an OAM of per photon, research on optical vortices has spread to various fields, including solid-state-device applications such as spintronics [2], information storage [3][4][5], processing [6][7][8], and quantum computation [9]. In such devices, information multiplexing using the OAM degree of freedom may significantly increase information capacity.…”
Section: Introductionmentioning
confidence: 99%